Nonlinear refraction in high terbium content borogermanate glass bulk and fiber - Henrique, Franciele R.; Pelosi, André G.; Almeida, Juliana M.P.; Franco, Douglas F. [UNESP]; Cocca, Leandro H.Z.; Clabel H., J. L.; Nalin, Marcelo [UNESP]; Mastelaro, V. R.; De Boni, L.; Mendonça, Cleber R. (Elsevier, 2024)
High terbium content glasses have stood out in technological areas due to their simultaneous ability of magnetization and transparency in the visible spectrum. Such magneto-optical glasses are relevant for several optical devices, including optical modulators, sensors, and isolators. While terbium ions are responsible for magnetic response, glass formers, and modifiers provide a branch of desirable mechanical, chemical, and optical properties, which can further be tailored by compositional manipulation. Determination of Verdet constant is usual in magneto-optical glass, however, little attention has been devoted to the determination of the optical properties, moreover the nonlinear ones. Herein, we investigate the nonlinear index of refraction (n2) of a novel magneto-optical glass shaped in bulk and optical fibers. Although the fabrication of fibers with high terbium content is challenging, the usage of optical fibers is important to improve signal that arises from magneto-optical and Kerr effects, since both depend on light propagation path. Bulk and optical fiber of 96(60GeO2-25B2O3–4Al2O3–10Na2O–1PbO) – 4Tb4O7 (mol%) glass were characterized by Z-scan and D-scan techniques, respectively, using femtosecond laser pulses. It was obtained the n2 spectrum in the range of 550–1200 nm for the former, which was modeled based on BGO model, revealing the role of oxygen ions for the optical nonlinearity. The optical fiber fabrication process does not compromise the n2 value, remaining n2=(5±2)×10−20m2/W at 790 nm according to D-scan measurements, which is equivalent to values determined by Z-scan, i.e. (6±2)×10−20m2/W. Additionally, the chemical states of the various elemental components of GBANP-4Tb glasses were investigated by X-ray photoelectron spectroscopy (XPS). The analysis of the Ge 3d and Tb 4f photoelectron spectra of the GBANP-4Tb glasses revealed the presence of Ge4+, Tb3+ and Tb4+ oxidation states. These results are relevant to expand the knowledge on magneto-optical materials, moreover regarding their optical response in the femtosecond regime, broadening its application in ultrafast magneto-optical devices.